Effects of Electronic Communication on the Mechanical Accuracy of Secondary School Students - Ambrose, Lynda (Universitas Ahmad Dahlan, 2023)
This study examined the effects of electronic communication on the mechanical accuracy of the written essays of private senior secondary school students in Oredo Local Government Area, Benin City, Edo State, Nigeria. The study employed a quantitative research approach with the use of questionnaires and direct observations as instrument used for data collection. The focus is on mechanical accuracy which involves grammar, punctuation and spelling (GPS) in the students’ essay writing. Private secondary schools in Oredo LGA in Edo State are 36, out of these, 10 schools were selected using the convenience sampling technique;15 students from each school were also purposively selected, making a total of 150 students. In all, 101 questionnaires were well filled out and retrieved successfully. However, the researcher rounded it up to 100. Simple percentage method was used to analyse the data. Results showed that 89% of the students make use of mobile phones for communication more than any other means of electronic media, while 64% used their phones for social networking. The results further showed an equilibrium in the percentage of students of whom the social network/communication affect their grammar and spelling which rates 41% each. Only 18% responded that it affected their punctuation. However, a close observation showed that inconsistent spelling, inappropriate use of punctuation marks, concord and wrong use of capitalisation are major pitfalls in the written essays of the senior secondary school students.